Национальные и этнические меньшинства в Польше в свете переписи населения 2002 года - Бабиньский, Г. (Социология: теория, методы, маркетинг, 2005)
The following article attempts to analyze and interpret the findings of the National
Census 2002 with respect to national and ethnic minorities. Apart from a concise
summary of numerical data from particular voivodships, much attention is paid to
such issues as: methodological remarks regarding questions about the respondents’
national identity entailed in the census and the effects of asking such questions,
factors distorting one’s declaration of national identity, some comments and reactions
of minorities to the census results. I hold a more analytic approach towards the three
biggest minorities: German, Ukrainian and Belarussian. The census results provide
many important data but only when we treat them as complementary information and
also when the numbers are somehow considered relative to the situation of a particular
minority, as well as the direction and stage of the situation’s change. Thanks to the
census we know much more about national and ethnic minorities in Poland. This
knowledge is, however, secondary, partial, allowing more for formulating hypotheses
than firm conclusions. For example we know for sure that there exists a Silesian
identification functioning as a basic ethnic identity, which cannot be narrowed to
regional one. However, we do not know much about the further evolution of this
community.